Particle Board Supply Chain Design from Palm Oil Solid Waste in West Borneo Province - Iwan Rusiardy; Muflihah Ramadhia; Donor Utomo Muhammad Susilo (SAFE-Network, 2026)
As the furniture industry develops, demand for wood-based particle board continues to increase, while the availability of wood from natural forests continues to decline. This situation has led to the need for sustainable alternative raw materials. Solid waste from oil palm in the form of empty fruit bunches (EFB) has great potential to be developed as a raw material for particle board. In West Kalimantan Province, the area of oil palm plantations reached 2,017,456 hectares in 2019, with a potential EFB production of around 7,470,639 tons. Therefore, this study aims to design an optimal supply chain network for the distribution of TKKS from palm oil processing plants in Sanggau Regency to particle board factories, as well as its distribution to all regencies/cities in West Kalimantan. The model developed uses a mixed-integer linear programming (MILP) approach to minimize total costs, including the costs of opening production sites, transportation, and distribution, while taking into account various constraints. The modeling results show that the optimal location for establishing a particle board factory is in Parindu District with a maximum capacity of 120,000 m³/year and a total investment of IDR 82,604,211,380.00. This model is expected to serve as the basis for long-term strategic decision-making for the West Kalimantan Provincial Government and be further developed by integrating TKKS as a by-product of the palm oil industry.